2016
DOI: 10.3791/53193
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the SH-SY5Y Human Neuroblastoma Cell Line

Abstract: Having appropriate in vivo and in vitro systems that provide translational models for human disease is an integral aspect of research in neurobiology and the neurosciences. Traditional in vitro experimental models used in neurobiology include primary neuronal cultures from rats and mice, neuroblastoma cell lines including rat B35 and mouse Neuro-2A cells, rat PC12 cells, and short-term slice cultures. While many researchers rely on these models, they lack a human component and observed experimental effects cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
332
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(360 citation statements)
references
References 34 publications
9
332
0
Order By: Relevance
“…SH‐SY5Y cells are a subclone of the parental neuroblastoma cell line SK‐N‐SH which contains both neuroblast‐like and epithelial‐like cells, they can be differentiated from a neuroblast‐like state into mature human neurons through a variety of different mechanisms including the use of RA, phorbol esters, and so on . The differentiated SH‐SY5Y cells represent a homogeneous neuronal population and similar to mature neurons and this makes SH‐SY5Y cells useful for a multitude of neurobiology experiments . Retinoic acid is one of the agents for inducing the differentiation of neuroblastoma cells .…”
Section: Resultsmentioning
confidence: 99%
“…SH‐SY5Y cells are a subclone of the parental neuroblastoma cell line SK‐N‐SH which contains both neuroblast‐like and epithelial‐like cells, they can be differentiated from a neuroblast‐like state into mature human neurons through a variety of different mechanisms including the use of RA, phorbol esters, and so on . The differentiated SH‐SY5Y cells represent a homogeneous neuronal population and similar to mature neurons and this makes SH‐SY5Y cells useful for a multitude of neurobiology experiments . Retinoic acid is one of the agents for inducing the differentiation of neuroblastoma cells .…”
Section: Resultsmentioning
confidence: 99%
“…Several approaches have been advanced for studying HSV infection in human neuron-like cells in culture, including the use of human neuroblastoma cell lines (24)(25)(26) and of a differentiated human embryonal carcinoma cell line (27,28). In addition, human neurons derived from induced pluripotent stem cells (iPSCs) (29), neuronal stem cells (30), and embryonic stem cells (ESCs) (31,32) have been explored as infection models for human alphaherpesvirus.…”
mentioning
confidence: 99%
“…It has been reported that retinoic acid can increase neurite outgrowth length by enhancing the differentiation of SH‐SY5Y cell (Shipley et al . ). The expression of VRK2 WT showed a significant reduction in the length of the longest neurite as compared with the GFP‐control in SH‐SY5Y cells, while neurite outgrowth in VRK2 KD over‐expression was partially rescued (Fig.…”
Section: Resultsmentioning
confidence: 97%